Daniel: A commentary on the book of Daniel - Collins, John Joseph; (1946-...) (U.S.A, 1993)
The most comprehensive English-language commentary on Daniel in 65 years. Collins situates the Old Testament in its historical context and offers a full explanation of the text, especially its religious imagery.
Keywords: Bible -- ST -- Book of Daniel -- influence